Analysis of the Utilization of Information Systems and Digital Communication Media on the Participation of Mothers of Toddlers in Posyandu - Yanuar Rachman Sadewa; Suryo Utomo; Faza Annasai; Moch. Septian Resi Wibowo (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2026)
The utilization of digital technology in health services, including posyandu activities, continues to increase; however, the participation of mothers of toddlers remains suboptimal. This study aimed to analyze the association between the utilization of information systems and digital communication media and the participation of mothers of toddlers in posyandu activities. A cross-sectional study was conducted in the working area of Sentolo I Primary Health Center, Kulon Progo, Yogyakarta, involving 60 respondents selected using total sampling. Data were collected using structured questionnaires and analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results showed that both information systems and digital communication media were significantly associated with participation (r = 0.41; p = 0.002 and r = 0.56; p < 0.001, respectively). Simultaneously, these variables contributed to participation (R² = 0.38), with digital communication media as the dominant factor (β = 0.47; p < 0.001). In conclusion, the integration of information systems and digital communication media is associated with increased participation of mothers of toddlers in posyandu activities. Strengthening digital literacy and optimizing communication strategies are recommended to improve participation in community-based health services